Value proposition evolution and the performance of internal corporate ventures - Covin, Jeffrey G.; Garrett, Robert P.; Kuratko, Donald F.; Shepherd, Dean A. (Journal of Business Venturing, 2015)
The success of internal corporate ventures (ICVs) is contingent upon their ability to: (1) anticipate the bases on which their offerings appeal to their target markets, (2) adjust these value propositions as the venture develops, and (3) leverage their parent corporations' relevant knowledge stocks. Aimed at developing a deeper understanding of the process requirements of successful exploratory initiatives, we build and test a model of venture performance using data from 145 ICVs. We find that value proposition evolution is related to venture performance in a curvilinear manner. ICVs whose value propositions exhibit moderate evolution perform better than ICVs whose value propositions exhibit no evolution or extensive evolution. Furthermore, the value proposition evolution–performance relationship is moderated by the parent corporation's familiarity with the venture's target market.